Internet use and learning behaviours of senior secondary school students in a local government area of Delta State, Nigeria (2020)
The purpose of this study is to investigate Internet use as a factor influencing learning behaviours (Competence Motivation, Attitude towards learning, Attention / Persistence on learning and Strategy to learning) of Senior Secondary School students in Sapele Local Government Area, Delta State, Nigeria. Three relevant objectives were set. Data were collected by means of questionnaires administered to 415 participants from among senior secondary school students using stratified random sampling. Descriptive statistics and inferential statistics with the aid of Statistical Package for Social Sciences (SPSS) were employed. Data were presented using frequency distribution, percentages, mean, Standard deviation, regression and correlation analysis. Findings revealed that senior secondary school students use the internet majorly for their school work and homework (x = 3.40, sd = 0.85), and to read book online (x = 3.20, sd = 0.98). Respondents use the internet to chat on a weekly basis (x = 3.70, sd = 1.50) and for school work and homework (x = 4.03, sd = 1.27). Respondents have a positive learning behaviours. Learning behaviours is relatively influenced by internet use (ß = 0.116, p < .05). There is a significant relationship between internet use and learning behaviours (r = .194, p < .05). The study recommends the need for school management to invest more in activities that will enhance internet use of students in schools. The school should invest in acquiring internet equipment and Information and communication technologies. These technologies will be geared towards the learning of students and will in turn boost the learning behaviours of students.